Systemic sclerosis and the heart - Parks, John L; Taylor, Marian H; Parks, Laura P; Silver, Richard M (Rheumatic diseases clinics of North America, 2014)
Heart disease, either clinically apparent or silent, is a frequent complication of systemic sclerosis (SSc, scleroderma) and may affect both patients with diffuse cutaneous and limited cutaneous SSc. The availability of more sensitive modalities has led to an increased awareness of scleroderma heart disease, which often involves the pericardium, myocardium, and cardiac conduction system. This awareness of cardiac involvement requires attention and interventions led by internists, cardiologists, and rheumatologists. Although no specific therapy exists for scleroderma heart disease, early recognition of the presence and type of scleroderma heart disease may lead to more effective management of patients with scleroderma.